PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA DI KELAS IV UPTD SDN 241 INPRES PERUMNAS TUMALIA - Sri Amalia Muhsin; Abd. Rahman Rahim; Anzar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low ability of elementary school students in writing descriptive texts. The purpose of this study was to determine the effect of the Project Based Learning model on the descriptive text writing ability of fourth grade students at UPTD SDN 241 Inpres Perumnas Tumalia. This research employed an experimental method a One Group Pretest-Posttest Design. The research subjects consisted of 16 students of class IV B. Data were collected through descriptive text writing test administered before the treatment (pretest) and after treatment (posttest). The data were analyzed using descriptive and inferential statistical analysis with the assistance of SPSS software. The results showed that there was an improvement in students’ descriptive text writing ability after the implementation of the Project Based Learning model. This was indicated by the average posttest score of 58,89 which was categorized as poor, while the average posttest score of 80,86 was categorized as good. The hypothesis testing using the Paired Sample t-Test showed a significance value (Sig. 2-tailed) of 0,000, which was lower than the significance level of 0,05 (0,000 < 0,05). Therefore, it can be concluded that the Project Based Learning model has a significant effect on the descriptive text writing ability of fourth grade students at UPTD SDN 241 Inpres Perumnas Tumalia.